Pengaruh Kualitas Produk dan Kualitas Pelayanan terhadap Kepuasan Konsumen pada Indomaret Cabang Jatirahayu - Dilla Dwi Puspita Sari; Natal Indra (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
Indomaret, as one of the largest convenience store chains in Indonesia, has become an important part of the lifestyle of urban communities. The rapid growth in the number of Indomaret outlets spread across various regions has made Indomaret the main destination for consumers looking for practical and easily accessible commodities and services. Research design is a type of research in which researchers design learning materials (such as learning activities and learning trajectories) for a particular topic and also at the same time build a theory about the learning process for that topic. Based on the results of the research that has been carried out, the results show that in the tests carried out on product quality variables, partial influence on purchasing decisions is significant. Based on the results of the t test carried out, it shows that the tcount value is greater than the ttable value, namely 4.392 2.322 with a significance level of 0.025 0.05. research results and discussion as well as hypothesis testing which aims to analyze the influence of product quality and service quality on consumer satisfaction.